2017
DOI: 10.1177/0018726717722395
|View full text |Cite
|
Sign up to set email alerts
|

The role of intermediaries in governance of global production networks: Restructuring work relations in Pakistan’s apparel industry

Abstract: This article locates the reorganization of work relations in the apparel sector in Pakistan, after the end of the Multi-Fibre Arrangement (MFA) quota regime, within the context of a global production network (GPN). We examine the role of a network of corporate, state, multilateral and civil society actors who serve as intermediaries in GPN governance. These intermediaries transmit and translate competitive pressures and invoke varied, sometimes contradictory, imaginaries in their efforts to realign and stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 58 publications
0
42
0
3
Order By: Relevance
“…However, our findings indicate that key actors involved in these compliance measures operate very much within the mandate prescribed by global brands and retailers. Munir et al (2017) reported similar findings in their analysis of global production networks in Pakistan's garment industry where transnational managerial elites played a key role in transforming governance regimes that served to protect the interests of western brands rather than those of workers.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 59%
“…However, our findings indicate that key actors involved in these compliance measures operate very much within the mandate prescribed by global brands and retailers. Munir et al (2017) reported similar findings in their analysis of global production networks in Pakistan's garment industry where transnational managerial elites played a key role in transforming governance regimes that served to protect the interests of western brands rather than those of workers.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 59%
“…For example, women from the Global South are frequently seen as oppressed, lacking confidence and in need of patronage from those in the North. As Munir et al (2018) showed, this image is often used to mobilize women to join factory work, often at a fraction of the wages that were being paid to men, hence not only producing inequality within local organizations but also maintaining the larger inequality between the Global North and South.…”
Section: Compensationmentioning
confidence: 99%
“…Exploitation is also often rife through global supply chains in which workers in the South are often mobilized into poorly paid, dangerous extractive and factory work (e.g., Hamann & Bartels, 2018;Munir et al, 2018). As Alamgir and Alakavuklar (2018) have shown in the case of the Bangladeshi garment manufacturing industry, monitoring worker abuse is difficult when multinationals engage with networks of subcontractors.…”
Section: Compensationmentioning
confidence: 99%
“…Recent literature has also more broadly explored the role and agency of various types of intermediaries in diffusing good labor practices through international supply networks. Munir, Ayaz, Levy, and Willmott (2018) scrutinized how corporate, state, multilateral, and civil society actors have served as intermediaries in global production network (GPN) governance. More closely related to our study's focus, Soundararajan, Khan, and Tarba (2018) highlight the role of sourcing agents as boundary spanners between Western buyers and local suppliers who contribute to labor standards in the Indian garment industry.…”
Section: Diffusion Of Sustainability Along Supply Networkmentioning
confidence: 99%